Relationship between the methylation levels of Twist gene and pathogenesis of endometriosis - Juanqing, Li; Hailan, Yu; Xiangwei, Fei; Tao, Zhang; Junyan, Ma; Jianhong, Zhou; Jun, Lin; Jianhua, Yang (Cellular and Molecular Biology, 2019)
The purpose of this study was to investigate the difference of Twist gene promoter methylation among ovarian ectopic endometrium, eutopic endometrium and non-endometriosis (EMs) endometrium . 15 patients with reproductive age hospitalized at Department of obstetrics and gynecology affiliated to Medicine School of Zhejiang University from January 2013 to June 2016 were selected. Among them, 5 patients underwent laparoscopic surgery due to ovarian type EMs, and were selected after histologic confirmation. Ectopic endometrium and eutopic endometrium were obtained simultaneously. Normal endometrium was obtained from 5 cases of tubal infertility confirmed by hysteroscopy. Six pairs of primers for CpG island of Twist gene promoter were designed, and the difference of promoter methylation levels was detected by pyrosequencing method for methylation specific PCR (MSP) in three groups of endometrial tissues. The promoter of Twist gene is hypomethylated in some areas of ovarian ectopic endometrium and eutopic endometrium of ovarian endometriosis. It is speculated that the regional hypomethylation of Twist gene promoter in ovarian ectopic endometrium and eutopic endometrium may cause over-expression of Twist protein, which may directly lead to the pathogenesis of endometriosis.